من صلحاء وعلماء بني راشد "أبو العباس أحمد بن يوسف الراشدي" - عبد الرحمن, عبد النور (University of Eloued جامعة الوادي, 2023)
ملخص: تهدف هذه الدراسة إلى تسليط الضوء على عالم من علماء بني راشد، عاش في القرن التاسع الهجري/الخامس عشر ميلادي، مجتهدا في سبيل التحصيل العلمي، فرحل من موطنه بني راشد إلى تلمسان ثم بعدها بجاية لتكتمل الرحلة الى البقاع المقدسة لأداء فريضة الحج وطلبا للمعرفة وبحثا عمن يستفيد منه، إنه أبو العباس أحمد بن محمد بن أحمد بن عبد الله بن يوسف الراشدي الملياني، من علماء المغرب الأوسط التي استفادت من الخزان العلمي لأحوازها وبواديها فأنجبت عدد هائل من الشيوخ والعلماء والأدباء والفقهاء. سنحاول في هذا المقال التعريف بشخصيته ورحلته إلى تلمسان وبجاية ولقائله مع أعلام التصوف والإحاطة بجميع جوانب رحلته وما نتج عنها من تأثر وتأثير في شخصيته، إضافة إلى تبيان إسهاماته العلمية من خلال المؤلفات التي تركها التي مزال البعض منها مخطوطا في المكتبات. الكلمات المفتاحية: قلعة بني راشد؛ أحمد بن يوسف الراشدي؛ الملياني؛ التصوف؛ المغرب الأوسط. Abstract: This study aims to shed light on a scholar of Bani Rashid in the Central Maghreb, He lived in the ninth century AH / fifteenth century AD, Diligent in pursuit of academic achievement, so he left from his homeland, Bani Rashid to Tlemcen, to complete the journey to Bejaia, in search of knowledge and in search of benefit from it. He is Abu al-Abbas Ahmad ibn Muhammad ibn Ahmad ibn Abdullah ibn Yusuf al-Rashidi al-Maliani. Among the scholars of the Middle Maghreb, which benefited from the scientific reservoir of its lands and valleys. It gave birth to a huge number of sheikhs, scholars, writers and jurists. In this article, we will try to introduce his personality, his journey to Tlemcen and Bejaia, and his encounters with the masters of Sufism. And take note of all aspects of his journey and the resulting impact and impact on his personality. In addition to showing his scientific contributions. Through the literature he left, some of which are still in manuscript form in libraries. key words: Bani Rashid Fort; Ahmed bin Youssef Al-Rashdi; the millionaire; Sufism; Central Maghreb.
مقال